2003
DOI: 10.1071/mf02153
|View full text |Cite
|
Sign up to set email alerts
|

Changes in biological parameters of Atlantic sharpnose shark Rhizoprionodon terraenovae in the Gulf of Mexico: evidence for density-dependent growth and maturity?

Abstract: Biological parameters of the Atlantic sharpnose shark Rhizoprionodon terraenovae in the northern Gulf of Mexico were re-examined to test for potential changes due to density dependent responses. Biological data from published studies in the Gulf of Mexico collected during the period 1979–1984 were compared with data collected during the period 1998–2001. For combined sexes, the von Bertalanffy growth parameters were L∞ = 110.8 cm total length, K = 0.39 year–1 and to = –0.86 year during 1984 and L∞ = 94.0 cm to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
105
3
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(113 citation statements)
references
References 15 publications
4
105
3
1
Order By: Relevance
“…The lack of older individuals can greatly affect growth model parameter estimates (Cailliet & Goldman 2004). Although researchers have suggested that changes in life history parameters over time many be the result of compensatory changes in response to anthropogenic factors such as fishing (Walker & Hislop 1998, Carlson & Baremore 2003, we do not believe that is the case for the cownose ray as no directed fishery exists for this species. Finally, these results may truly reflect differences in regional growth patterns.…”
Section: Discussionmentioning
confidence: 76%
“…The lack of older individuals can greatly affect growth model parameter estimates (Cailliet & Goldman 2004). Although researchers have suggested that changes in life history parameters over time many be the result of compensatory changes in response to anthropogenic factors such as fishing (Walker & Hislop 1998, Carlson & Baremore 2003, we do not believe that is the case for the cownose ray as no directed fishery exists for this species. Finally, these results may truly reflect differences in regional growth patterns.…”
Section: Discussionmentioning
confidence: 76%
“…Blacktip sharks have been heavily harvested in the Gulf of Mexico since the 1980's (NMFS 2003), thus the observed decrease in length-and age-atmaturity and increased growth rate lends support to the potential for a density-dependent compensatory response. Compensatory growth and reproductive responses have been documented in a few species of sharks (Sminkey and Musick 1995;Carlson and Baremore 2003). For reasons previously outlined, it could not be determined if these temporal changes in age and growth were due to differences in methodology, anthropogenic influences, or natural causes.…”
Section: Discussionmentioning
confidence: 95%
“…Sminkey and Musick (1995) found significant changes in length at age of several age classes of juvenile sandbar sharks, Carcharhinus plumbeus, following exploitation. Carlson and Baremore (2002) reported decreases in length and age at maturity in the Atlantic sharpnose shark, Rizoprionodon terraenovae, following exploitation. Cassof et al (2007) reported lower ages at maturity in the porbeagle, Lamna nasus, as a result of exploitation.…”
Section: Discussionmentioning
confidence: 96%